ANALISIS HUBUNGAN ANTARA SOCIAL MEDIA MARKETING dan ONLINE CUSTOMER REVIEW TERHADAP PURCHASE DECISION MELALUI TRUST PADA APLIKASI TIKTOK SEBAGAI MEDIA PEMASARAN - Pipit Ardianti; Putri Dwi Cahyani; Lusia Tria Hatmanti Hutami (Politeknik Bisnis Indonesia, 2023)
Tiktok is a social media application that is currently gaining popularity among the public, because its interesting features and easy access make TikTok one of the most popular applications. Tiktok was originally only used as social media which was only intended for entertainment, but now Tiktok is also used by people to promote their products. The study's overarching goal is to learn how consumers' confidence in the TikTok app affects their purchasing choices in relation to social media marketing and online customer reviews. The study used a purposive sample technique to collect data from 112 residents in Denpasar City. Surveys were sent out to gather data, which was then analyzed by multiple linear regression. The results show that trust significantly influences purchase decisions, social media marketing significantly influences trust, online customer reviews significantly impact trust, and trust significantly impacts purchase decisions.